2014
DOI: 10.1128/mcb.00472-14
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Dun1 Kinase Regulates Ribonucleotide Reductase Inhibitor Sml1 in Response to Iron Deficiency

Abstract: Iron is an essential micronutrient for all eukaryotic organisms because it participates as a redox-active cofactor in many biological processes, including DNA replication and repair. Eukaryotic ribonucleotide reductases (RNRs) are Fe-dependent enzymes that catalyze deoxyribonucleoside diphosphate (dNDP) synthesis. We show here that the levels of the Sml1 protein, a yeast RNR large-subunit inhibitor, specifically decrease in response to both nutritional and genetic Fe deficiencies in a Dun1-dependent but Mec1/R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 79 publications
3
47
1
Order By: Relevance
“…1, D and E, and 2, B and C). This was not a consequence of a reduction in Dun1-D328A protein abundance because its expression levels under low iron conditions were similar to those of wild-type Dun1 protein (47). These results reveal that Dun1 kinase activity is required for efficient nucleus-to-cytoplasm redistribution of RNR small subunit in response to iron deprivation and DNA damage.…”
Section: Dun1 Kinase Activity Is Essential For Subcellular Redistribumentioning
confidence: 58%
See 4 more Smart Citations
“…1, D and E, and 2, B and C). This was not a consequence of a reduction in Dun1-D328A protein abundance because its expression levels under low iron conditions were similar to those of wild-type Dun1 protein (47). These results reveal that Dun1 kinase activity is required for efficient nucleus-to-cytoplasm redistribution of RNR small subunit in response to iron deprivation and DNA damage.…”
Section: Dun1 Kinase Activity Is Essential For Subcellular Redistribumentioning
confidence: 58%
“…Then, Dun1 phosphorylates Sml1 protein, which is ubiquitylated and degraded to facilitate RNR activation under low iron conditions (47). We have also shown that the Rnr2-Rnr4 heterodimer is redistributed to the cytoplasm when iron availability is low (46).…”
Section: Dun1 Promotes Rnr2 and Rnr4mentioning
confidence: 71%
See 3 more Smart Citations